A method for corrugated differential rolling of a high bonding strength titanium-steel clad plate

By employing a corrugated variable-speed rolling composite method, which combines surface pretreatment, vacuum heating, corrugated rolling, and asynchronous rolling with tungsten inert gas welding, the problems of low bonding strength and brittle compound formation in titanium-steel composite plates have been solved, resulting in titanium-steel composite plates with high bonding strength and excellent plate shape quality.

CN123024764APending Publication Date: 2026-11-03TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161555.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve high bonding strength in titanium-steel composite plates without introducing an intermediate layer or relying on extreme rolling parameters, and effectively suppress the formation of brittle interfacial compounds, resulting in low interfacial bonding strength and easy delamination.

Method used

A corrugated variable-speed rolling composite method is adopted, including surface pretreatment, vacuum heating, corrugated rolling and asynchronous rolling, combined with tungsten inert gas welding for edge sealing, controlling the rolling temperature and deformation, and forming a tight metallurgical bond through dual shear strengthening and atomic diffusion.

Benefits of technology

It achieves high bonding strength and excellent plate shape quality in titanium-steel composite plates, avoids the introduction of intermediate layers and extreme rolling parameters, reduces raw material costs and simplifies the process, ensures no brittle compounds are generated at the interface, and possesses excellent bonding strength and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123024764A_ABST
    Figure CN123024764A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of metal composite material preparation, and discloses a corrugated differential speed rolling method for high bonding strength titanium steel composite plate. Specifically, after surface pretreatment of a steel substrate and a titanium plate, circumferential edge welding is performed by gas tungsten arc welding to form a composite slab; the composite slab is heated and kept at 880-920 DEG C in a vacuum environment, followed by double-pass composite rolling and heat treatment, and the product is obtained after cooling to room temperature; wherein the first pass adopts corrugated rolling, and strong shear deformation is used to promote plastic deformation of the difficult-to-deform steel substrate; the second pass adopts asynchronous rolling, and the interface fusion is strengthened by secondary shear deformation while the corrugation is rolled flat. Through the synergistic effect of "corrugated rolling+differential speed rolling", combined with GTAW edge sealing and vacuum heating, the present application effectively avoids interface oxidation and the generation of brittle compounds; the prepared titanium steel composite plate has significantly improved interface bonding strength and good deformation coordination, and is suitable for high-end equipment field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal composite material preparation technology, specifically to a method for corrugated variable-speed rolling composite of high-bonding-strength titanium-steel composite plates. Background Technology

[0002] Titanium-steel composite plates combine the excellent corrosion resistance and high specific strength of titanium alloys with the high strength, low cost, and economy of steel, making them promising for applications in chemical engineering, marine engineering, power and environmental protection, medical devices, and high-end equipment manufacturing. However, titanium and steel differ significantly in physical properties (such as coefficient of thermal expansion and modulus of elasticity) and crystal structure. Furthermore, titanium readily forms brittle Fe-Ti intermetallic compounds at high temperatures, resulting in low interfacial bonding strength and easy delamination. This has always been a technical bottleneck restricting the high-quality preparation of titanium-steel composite plates.

[0003] Currently, the main methods for preparing titanium-steel composite plates include: Explosive bonding method: It can achieve large-area bonding, but it generates a lot of noise and environmental pollution. Although the bonding interface is wavy, the quality fluctuates greatly, and the plate shape is difficult to control. It often requires a complicated leveling process afterward. Traditional hot rolling composite method: High production efficiency, but requires extremely high rolling force and reduction rate to ensure bonding. Due to the large difference in deformation resistance between titanium and steel, the flow of the difficult-to-deform steel metal is delayed during synchronous flat roll rolling, which easily leads to interfacial shear cracking; and in order to ensure bonding, high temperature and long time are usually required, which can easily lead to excessive growth of brittle phase and the formation of a continuous brittle layer. Intermediate layer assistance method: Although adding intermediate layers such as Cu, Ni, and V can block Ti-Fe diffusion, it increases the complexity of the process and the cost of raw materials. Furthermore, the introduction of intermediate layers may reduce the overall thermal conductivity or mechanical properties of the composite board and increase the risk of delamination.

[0004] In summary, the core problem commonly faced by existing technologies in the preparation of titanium-steel composite plates is: how to achieve a high-strength metallurgical bond between titanium and steel, effectively suppress or control the formation of harmful brittle compounds at the interface, and ensure excellent plate shape quality of the composite plate through effective process means without introducing an additional intermediate layer or relying on extreme rolling parameters. Summary of the Invention

[0005] In view of the above, the present invention aims to provide a corrugated variable-speed rolling composite method for high-bonding-strength titanium-steel composite plates to solve the above-mentioned problems in the prior art; the method can significantly improve the bonding strength of the titanium / steel interface without introducing an intermediate layer, effectively control the formation of brittle interfacial compounds, and improve the deformation coordination of the two metals.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for corrugated, high-strength titanium-steel composite plate rolling composite, comprising the following steps: S1. Surface pretreatment: The surfaces of the steel substrate and titanium plate to be bonded are pretreated to remove the oxide layer and expose the fresh metal. S2. Assembly and edge sealing: The pretreated titanium plates are stacked on the steel substrate, and the edges are sealed by tungsten inert gas welding (GTAW) to form a closed composite plate blank. S3. Vacuum heating: Place the welded composite slab in a vacuum heating furnace, heat it to 880–920℃ in a vacuum environment and keep it at that temperature for a certain time. S4. First Corrugated Rolling: The heated composite slab is immediately subjected to the first corrugated rolling: corrugated rolls and flat rolls are paired, and the corrugated rolls are in contact with the side of the steel plate. S5. Second pass asynchronous rolling: The slab after the first pass rolling is not heated in the middle and is directly subjected to the second pass asynchronous rolling: upper and lower flat rolls are used, and the upper roll and the lower roll have a difference in linear speed to flatten the corrugations and perform compound rolling. S6. Cooling: The rolled composite plate is cooled to room temperature by a combination of furnace cooling and air cooling to obtain the finished titanium-steel composite plate.

[0007] Furthermore, the surface pretreatment in S1 includes: first grinding the steel substrate and titanium plate surface with an angle grinder until the roughness Ra≤3.2 μm, then wiping with anhydrous ethanol and drying with hot air, and proceeding to S2 within 30 min after the treatment is completed.

[0008] Furthermore, the GTAW welding parameters in S2 are as follows: the welding wire is copper-nickel welding wire (Cu70Ni30) with a diameter of 1.0 mm, the welding current is 80–120 A, the voltage is 10–15 V, and the welding speed is 3–8 mm / s.

[0009] Furthermore, in S3, the vacuum degree is ≤5×10⁻⁶. -2 Pa, heating rate 5–10 ℃ / min, holding time 1–1.5h.

[0010] Furthermore, in S4, the corrugated section of the corrugated roll used in corrugated rolling is a sine wave, and the reduction rate is selected in the range of 20–30%.

[0011] Furthermore, in the S5 asynchronous rolling process, the ratio of the linear velocities of the upper and lower rolls is 1.1–1.3, and the reduction rate is selected from 15–25%.

[0012] Furthermore, the cooling method in S6 is furnace cooling: the temperature is reduced to 500 ℃ at a rate of ≤15 ℃ / min and then air-cooled after exiting the furnace.

[0013] This invention specifically addresses the significant difference in plastic deformation capabilities between titanium and steel. It employs a two-pass synergistic deformation process combining corrugated rolling and asynchronous rolling. The first pass, corrugated rolling, utilizes sinusoidal rolls to apply localized strong shear, forcing the difficult-to-deform steel matrix to undergo plastic flow, effectively breaking down the oxide film and forming macroscopic mechanical interlocking. The second pass, asynchronous rolling, utilizes the "rolling" effect generated by the speed difference, introducing secondary shear while flattening the corrugations, promoting atomic diffusion, thus achieving extremely high bonding strength with a relatively small total deformation. Circumferential edge sealing is achieved using tungsten inert gas welding combined with vacuum heating, effectively isolating oxygen and fundamentally preventing interface oxidation before and during rolling. Simultaneously, precise temperature control (880–920℃) ensures sufficient metal plasticity while maximally suppressing excessive interdiffusion of titanium and iron atoms, effectively controlling the formation and growth of the brittle Fe-Ti intermetallic compound layer, resulting in a clean and tough composite interface.

[0014] The beneficial effects of this invention are as follows: By adopting a dual-pass synergistic deformation process of "corrugated rolling + asynchronous rolling", a combination of dual shear strengthening is achieved: strong shear deformation preferentially promotes the plastic flow of the relatively difficult-to-deform steel matrix, improves the deformation coordination between the two during the rolling process, reduces the concentration of interfacial shear stress, and avoids interfacial slippage or cracking; by using tungsten inert gas welding for circumferential edge sealing, combined with vacuum heating, the oxidation of the interface before and during rolling is fundamentally avoided, effectively controlling the formation and growth of the brittle Fe-Ti intermetallic compound layer, and obtaining a clean and tough composite interface; the entire process does not require the introduction of intermediate layer materials such as copper and nickel, effectively simplifying the process and reducing raw material costs; this process has relatively mild requirements on the mill tonnage, does not require extreme rolling parameters, and is easy to realize industrial production. Attached Figure Description

[0015] Figure 1 This is a process flow diagram of the preparation method of the present invention; Figure 2 This is a schematic diagram of the interface SEM microstructure of the titanium-steel composite plate prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope (SEM) image of the interface shear fracture surface of the titanium-steel composite plate prepared in Example 1 of the present invention. Detailed Implementation

[0016] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Referring to the figures shown, the composite board is processed according to the given process flow. Example 1

[0017] This embodiment 1 describes the preparation of a 304 stainless steel / TA2 pure titanium composite plate. The specific steps are as follows: S1. Surface pretreatment: Select 304 stainless steel plate (3mm thick) and TA2 titanium plate (2mm thick). Grind the surfaces to be joined using an angle grinder, controlling the roughness Ra to be approximately 2.5 μm. Wipe with anhydrous ethanol and dry with hot air, completing the assembly within 20 minutes. S2. Assembly welding: GTAW edge sealing welding is used. The welding wire is Cu70Ni30 (φ1.0 mm), the welding current is 100 A, the voltage is 12 V, and the welding speed is 5 mm / s. S3. Vacuum heating: Place the slab in a vacuum furnace and evacuate the vacuum level to 3×10⁻⁶. -2 Pa. The temperature was increased to 900℃ at a rate of 8℃ / min and held for 1.2 hours; S4. First pass of corrugated rolling: This is performed immediately after the rolls are removed from the vacuum furnace. The corrugated rolls contact the steel substrate, and the waveform is sinusoidal. The reduction rate is controlled at 25%. S5. Second asynchronous rolling: After the first rolling is completed, the second rolling is carried out immediately without reheating in the furnace; upper and lower flat rolls are used, the speed ratio (upper roll linear speed / lower roll linear speed) is set to 1.2, the reduction rate is controlled at 20%, and the corrugations are rolled flat. S6. Cooling: Cool the furnace at a rate of 10 ℃ / min to 500℃, and then air cool it to room temperature after removing it from the furnace.

[0018] Results: Testing showed that the composite board's interfacial shear strength reached 365 MPa, indicating good bonding and no delamination. Figure 2 , 3 As shown in the attached diagram, a textual explanation is provided.

[0019] Performance test results: The titanium-steel composite plate prepared in this embodiment has good interfacial bonding, with no delamination, cracking, or unbonded defects, and the interfacial shear strength reaches 365 MPa. As shown in Figure 2, the interface SEM microstructure shows that the titanium layer and the steel matrix have a continuous and smooth interface, without visible defects such as pores or cracks. There is no obvious continuous distribution of brittle Fe-Ti intermetallic compound layer at the interface, and the titanium and steel have achieved a tight metallurgical bond. As shown in Figure 3, the interface shear fracture surface has a large number of uniformly distributed dimples and obvious tear ridges, exhibiting typical ductile fracture characteristics, without brittle cleavage fracture morphology, confirming that the composite plate interface has excellent bonding strength and toughness. Example 2

[0020] In Example 2, a 316L steel / TA1 pure titanium composite plate was prepared. The specific steps are as follows: S1. Surface pretreatment: Select 316L steel plate (4mm thick) and TA1 titanium plate (2mm thick). Grind the surfaces to be joined using an angle grinder, controlling the roughness Ra to be approximately 3.0 μm. Wipe with anhydrous ethanol and dry with hot air, completing the assembly within 25 minutes. S2. Assembly welding: GTAW edge sealing welding is adopted, the welding wire is Cu70Ni30 (φ=1.0 mm), the welding current is 80 A, the voltage is 10 V, and the welding speed is 3 mm / s; S3. Vacuum heating: Place the slab in a vacuum furnace and evacuate the vacuum level to 2×10⁻⁶. -2 Pa. The temperature was increased to 880℃ at a rate of 5℃ / min and held for 1.5 hours; S4. Corrugated Rolling: The first rolling pass is performed immediately after removal from the steel substrate. The corrugated rolls contact the steel substrate, the waveform is sinusoidal, and the reduction rate is controlled at 20% (lower limit). S5. Asynchronous rolling: No reheating is performed; the second rolling pass is performed immediately. Upper and lower flat rolls are used, with the speed ratio (upper roll linear speed / lower roll linear speed) set to 1.1, and the reduction rate controlled at 15% (lower limit). S6. Cooling: After cooling to 500℃ in the furnace at 12℃ / min, remove from the furnace and air cool to room temperature.

[0021] Results: Although the heating temperature and deformation were both at the lower limit, metallurgical bonding was still achieved at the interface by means of corrugation and asynchronous double shearing, with a shear strength of 340 MPa and a flat plate shape. Example 3

[0022] In Example 3, a 316H steel / TC4 titanium alloy composite plate was prepared. The specific steps are as follows: S1. Surface pretreatment: Select Q345 steel plate (12mm thick) and TC4 titanium alloy plate (3mm thick). Grind the surfaces to be joined using an angle grinder, controlling the roughness Ra to be approximately 2.8 μm. Wipe with anhydrous ethanol and dry with hot air, completing the assembly within 20 minutes. S2. Assembly welding: GTAW edge sealing welding is adopted, the welding wire is Cu70Ni30 (φ=1.0 mm), the current is 120 A, the voltage is 15 V, and the welding speed is 8 mm / s; S3. Vacuum heating: Place the slab in a vacuum furnace and evacuate the vacuum level to 4×10⁻⁶. -2 Pa. The temperature was increased to 920℃ at a rate of 10℃ / min and held for 1.0 hour; S4. Corrugated Rolling: The first rolling pass is performed immediately after removal from the steel substrate. The corrugated rolls contact the steel substrate, the waveform is sinusoidal, and the reduction rate is controlled at 30% (upper limit). S5. Asynchronous rolling: No reheating is performed; the second rolling pass is performed immediately. Upper and lower flat rolls are used, with the speed ratio (upper roll linear speed / lower roll linear speed) set to 1.3 (upper limit), and the reduction rate controlled at 25% (upper limit). S6. Cooling: Cool to 500℃ in the furnace at 8℃ / min, and then air cool to room temperature after exiting the furnace.

[0023] Results: The interfacial shear strength reached 380 MPa, the microscopic observation showed extremely deep interlocking, and the compound layer thickness was less than 1.5 μm. Comparative Example 1

[0024] The difference between Comparative Example 1 and Example 1 is that: in step S4, corrugated rolls are not used, but flat rolls are used for ordinary synchronous rolling, that is, both passes are flat rolls, the first pass has no corrugated features, and the reduction rate is maintained at 25%; the remaining steps are the same as in Example 1.

[0025] Result: Due to the lack of strong shearing action in the first pass, the oxide film on the surface of the steel substrate was not completely broken, resulting in unbonded areas at the interface and a shear strength of only 210 MPa. Comparative Example 2

[0026] The difference between Comparative Example 2 and Example 1 is that: in step S5, ordinary synchronous rolling is used, that is, the linear speeds of the upper and lower rolls are equal and the speed ratio is 1.0. The remaining steps are the same as in Example 1.

[0027] Results: Although the first pass of corrugated rolling formed a mesh, the second pass lacked the "rolling" shear force of asynchronous rolling, the atomic diffusion at the interface was insufficient, and the residual stress was large during the process of flattening the corrugations; the shear strength was 290 MPa, and the flatness of the plate was poor. Comparative Example 3

[0028] The difference between Comparative Example 3 and Example 1 is that the heating temperature in step S3 is 800°C, which is lower than the 880-920°C range required by the present invention; the remaining steps are the same as in Example 1.

[0029] Results: The steel matrix lacked plasticity, and the deformation resistance was too large during the corrugated rolling process. This resulted in the titanium plate being over-compressed while the steel plate deformed very little. The interface failed to form an effective physical bond, and delamination occurred after rolling, with no bonding strength. Comparative Example 4

[0030] The difference between Comparative Example 4 and Example 1 is that the heating temperature in step S3 is 1000℃, which is higher than the range required by the present invention; the remaining steps are the same as in Example 1.

[0031] Results: Although bonding was achieved, the high temperature at the interface caused intense diffusion of Ti and Fe atoms, resulting in a continuous brittle intermetallic compound layer with a thickness exceeding 5 μm. The compound exhibited brittle fracture in shear tests, with its strength decreasing to 160 MPa.

[0032] This invention achieves dual shear strengthening by employing a two-pass synergistic deformation process of "corrugated rolling + asynchronous rolling." Comparing the composite plate properties obtained in the embodiments and comparative examples, the titanium-steel composite plate prepared in this invention exhibits good interfacial bonding, with no delamination, cracking, or unbonded defects, no obvious warping, and a flat plate shape. The interfacial shear strength reaches over 340 MPa. Specific properties are described in Table 1. The shear strength of the composite plate obtained in the comparative examples is significantly improved. As shown in Figure 2 (interfacial SEM microstructure), the titanium layer and steel matrix interface are continuously and smoothly bonded, without visible pores or cracks. There is no obviously continuous brittle Fe-Ti intermetallic compound layer at the interface, indicating a tight metallurgical bond between titanium and steel. As shown in Figure 3 (interfacial shear fracture morphology), the fracture surface exhibits numerous uniformly distributed dimples and obvious tear ridges, exhibiting typical ductile fracture characteristics, without brittle cleavage fracture morphology, confirming the excellent bonding strength and toughness of the composite plate interface.

[0033] Table 1. Description of the properties of composite panels in the examples and comparative examples. Group Shear strength (MPa) Warpage degree / Plate shape quality Example 1 365 No obvious warping, flat board shape Example 2 340 No obvious warping, flat board shape Example 3 380 No obvious warping, flat board shape Comparative Example 1 210 Poor Comparative Example 2 290 Slight warping Comparative Example 3 0 (layer) Range Comparative Example 4 160 MPa Slight warping The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for corrugated, variable-speed rolling composite of high-strength titanium-steel composite plates, characterized in that, Includes the following steps: S1. Surface pretreatment: The surfaces of the steel substrate and titanium plate to be bonded are pretreated. Specifically, the surfaces of the steel substrate and titanium plate are first ground with an angle grinder until the roughness Ra≤3.2 μm, then wiped with anhydrous ethanol and dried with hot air. After treatment, proceed to S2 within 30 minutes. S2. Assembly and edge sealing: The pretreated titanium plates are stacked on the steel substrate, and the edges are sealed by tungsten inert gas welding to form a sealed composite plate blank. S3. Vacuum heating: Place the welded composite slab in a vacuum heating furnace, with a vacuum degree ≤5×10⁻⁶. -2 Pa, heating rate 5–10 °C / min, heated to 880–920 °C in a vacuum environment and held for 1–1.5 h; S4. First pass of corrugated rolling: Corrugated rolls and flat rolls are paired together, and the corrugated rolls contact the side of the steel plate to immediately roll the heated composite slab. S5. Second pass asynchronous rolling: The composite slab after the first pass rolling is not heated in the middle, but is directly subjected to asynchronous rolling. Upper and lower flat rolls are used, and the upper and lower rolls have a difference in linear speed to smooth the corrugations and perform composite rolling. S6. Cooling: The rolled composite plate is cooled to room temperature by a combination of furnace cooling and air cooling to obtain the finished titanium-steel composite plate.

2. The method for corrugated variable-speed rolling composite of high-bonding-strength titanium-steel composite plates according to claim 1, characterized in that, The welding parameters for tungsten inert gas (TIG) shielded welding in S2 are as follows: copper-nickel welding wire with a diameter of 1.0 mm, welding current of 80–120 A, voltage of 10–15 V, and welding speed of 3–8 mm / s.

3. The method for corrugated variable-speed rolling composite of high-bonding-strength titanium-steel composite plates according to claim 1, characterized in that, In S4, the corrugated section of the corrugated roll used in corrugated rolling is a sine wave, and the reduction rate is selected in the range of 20–30%.

4. The method for corrugated variable-speed rolling composite of high-strength titanium-steel composite plates according to claim 1, characterized in that, In the S5 asynchronous rolling process, the ratio of the linear speeds of the upper and lower rolls is 1.1–1.3, and the reduction rate is selected from 15–25%.

5. The method for corrugated variable-speed rolling composite of high-strength titanium-steel composite plates according to claim 1, characterized in that, In the S6 cooling process, the furnace is cooled to 500°C at a rate of ≤15°C / min, and then the furnace is air-cooled.